2024
DOI: 10.1037/rmh0000247
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and service providers’ perspectives of services for autism in the rural region of Northern Arizona.

Katherine A. Feather,
Olivia J. Lindly,
Lisa Persinger
et al.

Abstract: Children with autism and their families living in rural settings face significant barriers when accessing adequate diagnostic, treatment, and care coordination services. This mixed-method study examined services used for children with autism in rural Northern Arizona using a parent-reported (N = 49) and service provider-reported (N = 36), online survey. Results indicated that parents on average experienced a delay in diagnosis with limited access to professional services, such as care coordination. Findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Bhat (2021) found families with higher socioeconomic status, younger children with ASD, or children requiring substantial support reported lower benefits from telehealth services. Feather et al (2024) also found that during the pandemic, parents living in rural communities were dissatisfied with the use of telehealth services, and service providers should assess whether a child is appropriate for telepractice or would be better served in person. Alternatively, children requiring minimal support and families of older children with ASD indicated online services were significantly beneficial, as the elimination of travel reduced the additional burden for caregivers (Bhat, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bhat (2021) found families with higher socioeconomic status, younger children with ASD, or children requiring substantial support reported lower benefits from telehealth services. Feather et al (2024) also found that during the pandemic, parents living in rural communities were dissatisfied with the use of telehealth services, and service providers should assess whether a child is appropriate for telepractice or would be better served in person. Alternatively, children requiring minimal support and families of older children with ASD indicated online services were significantly beneficial, as the elimination of travel reduced the additional burden for caregivers (Bhat, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By attending to the caregivers’ well-being and checking in with their stress levels during times of crisis, service providers can support the adjustment and provide targeted interventions, whether for the caregiver or suggestions on how to manage their child’s symptoms. Feather et al (2024) found that targeted knowledge- and skill-focused mediated interventions to be extremely helpful to combat parental fatigue and boost well-being. Further, parent-mediated intervention programs can help parents improve the main problematic areas of their child’s core ASD symptoms (Feather et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations